A Direct Imaging Method for Inverse Electromagnetic Scattering Problem in Rectangular Waveguide (Communications in Computational Physics, 2018)
We propose a direct imaging method based on reverse time migration (RTM)algorithm for imaging extended targets using electromagnetic waves at a fixed frequencyin the rectangular waveguide. The imaging functional is defined as the imaginarypart of the cross-correlation of the Green function for Helmholtz equation and theback-propagated electromagnetic field. The resolution of our RTM method for penetrableextended targets is studied by virtue of Helmholtz-Kirchhoff identity in the rectangulardomain, which implies that the imaging functional always peaks in the target.Numerical examples are provided to demonstrate the powerful imaging quality andconfirm our theoretical results.